Product Design Development of Syfoin using House of Quality - Johannes, Diva Gloria; Handayati, Yuanita (Proceedings International Conference on Education Innovation and Social Science, 2023)
This research attempts to address the business problem that SYFO is currently experiencing, particularly the difficulty of boosting sales and enhancing customer retention for their meal kit product. To discover areas of unhappiness, the search starts by interviewing past clients. The results show a mismatch between client expectations and the business's offers, which calls for a more thorough inquiry using business and root cause analysis. Lack of resources and unambiguous standards for incorporating consumer preferences into product design are determined to be the root of SYFO's issue. Customer preference attributes, technical preference attributes, and information on priority levels are gathered from literature reviews and 102 respondents using the House of Quality (HOQ) framework. The effectiveness of SYFO's products is compared to that of Sumibi and reFresh. The result of the HOQ framework indicates areas that need improvement in the prior product design and offers a priority list for product development. The suggested remedies to the problems mentioned include finding special ingredients and creating appealing, useful packaging.